A quantum chemical study from a molecular transport perspective: ionization and electron attachment energies for species often used to fabricate single-molecule junctions - Bâldea, Ioan (Organic photonics and electronics, 2014)
The accurate determination of the lowest electron attachment (EA) and ionization (IP) energies for molecules embedded in molecular junctions is important for correctly estimating, for example, the magnitude of the currents (I) or the biases (V) where an I-V curve exhibits significant non-Ohmic behavior. Benchmark calculations for the lowest electron attachment and ionization energies of several typical molecules utilized to fabricate single-molecule junctions characterized by n-type conduction (4,4′-bipyridine, 1,4-dicyanobenzene and 4,4′-dicyano-1,1′-biphenyl) and p-type conduction (benzenedithiol, biphenyldithiol, hexanemonothiol and hexanedithiol) based on the EOM-CCSD (equation-of-motion coupled-cluster singles and doubles) state-of-the-art method of quantum chemistry are presented. They indicate significant differences from the results obtained within current approaches to molecular transport. The present study emphasizes that, in addition to a reliable quantum chemical method, basis sets much better than the ubiquitous double-zeta set employed for transport calculations are needed. The latter is a particularly critical issue for correctly determining EAs, which is impossible without including sufficient diffuse basis functions. The spatial distribution of the dominant molecular orbitals (MOs) is another important issue, on which the present study draws attention, because it sensitively affects the MO energy shifts Φ due to image charges formed in electrodes. The present results cannot substantiate the common assumption of a point-like MO midway between electrodes, which substantially affects the actual Φ-values.
Gesehen am 24.02.2021